2021
DOI: 10.21873/invivo.12638
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel and CarboplatinVersusCisplatin and 5-Fluorouracil in Concurrent Chemoradiotherapy in Patients With Esophageal Cancer

Abstract: Background/Aim: Cisplatin with 5-fluouracil (Cis/5Fu) and paclitaxel with carboplatin (Pac/Car) are common regimens used in concurrent chemoradiotherapy (CCRT) for patients with locally advanced esophageal cancer (EC). Here, we aimed to compare the survival outcomes and treatment-related toxicities between these regimens in neoadjuvant CCRT in patients with locally advanced EC. Patients and Methods: One hundred and thirty-six patients with locally advanced EC (98% squamous cell carcinoma) were prospectively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Through preliminary inspection, a total of 1300 relevant studies were obtained, including 1298 which met the inclusion criteria and 2 similar reading articles. After further screening, 34 articles were obtained for further evaluation [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Among these studies, the chemotherapy regimen of one and the study objects of two did not meet the inclusion criteria. Finally, a total of 31 articles involving 3432 participants were included [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The detailed retrieval process of this review is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…One study showed that neoadjuvant CRT with carboplatin and paclitaxel doublet is associated with a better survival outcome, higher surgical resection rate, and better safety profiles than cisplatin and capecitabine in patients with locally advanced esophageal SCC. However, pCR was not examined [20].…”
Section: Discussionmentioning
confidence: 99%
“…The role of systemic inflammation has been a topic of interest in several fields of oncology (11,12). While several biomarkers have been widely used to reflect the nutritional and inflammatory status of cancer patients, their roles in different malignancy types and treatment settings have established different predictive or prognostic roles.…”
Section: Discussionmentioning
confidence: 99%